163k views
4 votes
36 squared-46-22=0 quadratic formula

1 Answer

5 votes
Your question isn't quite formatted correctly to be a quadratic equation as it has no variable for the "a" and "b" terms but I'll just insert them and hopefully it will match what you're asking.

Let x be our variable.

36x² - 46x - 22

The quadratic formula for a quadratic equation in the format ax² + bx + c = 0 is:


x = \frac{- b +/- \sqrt{b^(2) - 4ac} }{2a}

Now we just insert our terms to the formula:

x = \frac{46 +/- \sqrt{(-46)^(2) - 4(36)(-22)} }{2(36)}

And now we solve:

x = (46 +/- √(2116 + 3168))/(72)

x = (46 +/- √(5284))/(72)

x = (46 +/- 2√(1321))/(72)

Your final answers when you simplify:


x = (23 + √(1321) )/(36) and
x = (23 - √(1321))/(36)
User Serge Roussak
by
5.1k points